Pengelolaan Praktik Kerja Industri (Prakerin) Di SMK Negeri I Tengaran Kabupaten Semarang - SETYATI, SIWI PUJI; , Prof. Dr. Sutama, M.Pd; , Dr. Sumardi, M.Si (2015)
The purpose of this study was to describe the characteristics Industrial Work Practices management planning, the implementation and oversight in Private Vocational High School 1 Tengaran. This research is a qualitative study research design phenomenological. Technique used observation, of interview and documentation, analyzed using with reduction, data presentation, and conclusion. The validit used credibility test, test transferability, dependability test, and test convertibility. The results showed managed with strict rules and binding and based on the work order. The implementation of with due regard to the functions and objectives of planned by the Working Group on Industrial Relations and his staff authorized by the Principal at the beginning of the school year as outlined in the work program of industrial relations then distributed to teachers to monitor the students gradually.